2018
DOI: 10.31234/osf.io/zvm9a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The New Statistics for Neuroscience Majors: Thinking in Effect Sizes

Abstract: This paper has now been published in the Journal of Undergraduate Neuroscience Eduction: http://www.funjournal.org/wp-content/uploads/2018/04/june-16-e21.pdf?x91298. See also, this record on PubMed and PubMedCentral: https://www.ncbi.nlm.nih.gov/pubmed/30057503. An ongoing reform in statistical practice is to report and interpret effect sizes. This paper provides a short tutorial on effect sizes and some tips on how to help your students think in terms of effect sizes when analyzing data. An effect size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…The peak t -value was found in the gray matter of the left posterior superior temporal gyrus [ t (21) = 3.65, P < 0.002, d = 0.76; Figure 5 , middle upper panel], the other areas composing the cluster comprised parts of the supramarginal gyrus and the rolandic operculum. With d = 0.76 we report a close to large effect size here (Cohen, 1988 ; Calin-Jageman, 2018 ).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The peak t -value was found in the gray matter of the left posterior superior temporal gyrus [ t (21) = 3.65, P < 0.002, d = 0.76; Figure 5 , middle upper panel], the other areas composing the cluster comprised parts of the supramarginal gyrus and the rolandic operculum. With d = 0.76 we report a close to large effect size here (Cohen, 1988 ; Calin-Jageman, 2018 ).…”
Section: Resultssupporting
confidence: 71%
“…These analyses demonstrated that the AP group was significantly more accurate than the NAP group (see Figure 3 , Table 2 ). The test yielded a large effect size [ R 2 m = 0.69; (Cohen, 1988 ; Calin-Jageman, 2018 )]. The NAP groups showed a less homogeneous performance than the AP group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…if not "large" (0.8) [29], which would require 64 or 26 animals per group, respectively, in order to ensure adequate power ( Table 5). Setting the minimum effect size is not something to be fixed, and depends not only on the assay but also on the investigator's hypothesis to be tested [30].…”
Section: But the Power Of Current Fst Assays Is Adequate Isn't It?mentioning
confidence: 99%